2006
DOI: 10.1111/j.1600-0609.2006.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities of young multiple myeloma patients (<45 yr) are not different from those of other age groups and are independent of stage according to the International Staging System

Abstract: Little is known about tumor-related prognostic factors, in particular specific chromosomal abnormalities, in young patients with multiple myeloma (MM). We therefore investigated the chromosomal pattern by interphase fluorescence in situ hybridization (chromosomes 13q14, 14q32-translocations, chromosomes associated with hyperdiploidy) in 38 young patients with MM (age <45 yr) and compared the results with those observed in 69 patients with intermediate age (45-70 yr) and 64 elderly patients (age >70 yr). All ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
8
2
Order By: Relevance
“…This agrees with previous findings obtained in 2 smaller studies that did not reveal any association between cytogenetic aberrations and age in a cohort of 75 patients 24 and in another group of 172 patients. 25 In the latter study, similar frequencies of chromosomal aberrations have been observed in 3 cohorts of patients with different age definitions (younger than 45 years, 45 to 70 years, and older than 70 years) and in all ISS stages. This is in disagreement with a report that indicated a decreasing frequency of IgH translocations with increasing age.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This agrees with previous findings obtained in 2 smaller studies that did not reveal any association between cytogenetic aberrations and age in a cohort of 75 patients 24 and in another group of 172 patients. 25 In the latter study, similar frequencies of chromosomal aberrations have been observed in 3 cohorts of patients with different age definitions (younger than 45 years, 45 to 70 years, and older than 70 years) and in all ISS stages. This is in disagreement with a report that indicated a decreasing frequency of IgH translocations with increasing age.…”
Section: Discussionsupporting
confidence: 64%
“…The data were, however, not corrected for differences in general life expectancy between these age groups. Other studies such as the analysis of the data of International Blood and Bone Marrow Registry 16 in patients aged younger than 60 years and 60 years and older, and data from Little Rock 17 in patients aged younger (25) .034…”
Section: Discussionmentioning
confidence: 99%
“…The survival outcome reported in our study was similar to those of previous reports6,10,11 but was different from the results reported by Cheema et al,12 who found a trend toward prolonged OS and PFS in patients under the age of 50 only in patients treated with bortezomib.…”
Section: Discussionsupporting
confidence: 51%
“…Younger age has been reported to be correlated with improved survival and has been recognized as an important prognostic factor 6,10,11. However, when undergoing upfront autologous stem cell transplant, age below 40 years does not confer a superior prognosis in patients with MM 12.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, dose reduction of bortezomib is not required, since plasma clearance is <90 min. Bortezomib and bortezomib-based regimens overcome the increased drug resistance inferred by cytogenetic risk factors [del13, t(4;14)] [17].…”
Section: Conventional Therapy With New Drugs Thalidomidementioning
confidence: 99%